2011
DOI: 10.1007/s00467-011-2086-4
|View full text |Cite
|
Sign up to set email alerts
|

Linear nevus sebaceous syndrome with hypophosphatemic rickets with elevated FGF-23

Abstract: It is possible that an as-yet unidentified substance increases FGF-23 expression LNS lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…We studied the effects of epidermal nevus ablation, and found that neither surgical excision nor laser ablation correlated with improvement in mineral status or patient-reported quality of life. Immunolocalization and qPCR studies did not detect FGF23 expression within nevi from all 5 patients, consistent with prior reports [19]. …”
Section: Reviewsupporting
confidence: 91%
See 1 more Smart Citation
“…We studied the effects of epidermal nevus ablation, and found that neither surgical excision nor laser ablation correlated with improvement in mineral status or patient-reported quality of life. Immunolocalization and qPCR studies did not detect FGF23 expression within nevi from all 5 patients, consistent with prior reports [19]. …”
Section: Reviewsupporting
confidence: 91%
“…While some case reports suggest a therapeutic response, the results are confounded by concomitant oral medication or lack of follow-up. CSHS/nevus syndrome patients may undergo potentially painful removal procedures with no improvement [13, 19]. Not all patients in whom phosphate levels normalized were subject to nevi removal and there is evidence that phosphaturia improves over time [44].…”
Section: Reviewmentioning
confidence: 99%
“…It has been proposed that FGF23 is the putative phosphatonin, based on demonstration of its elevated blood levels in a patient with LNSS (56). Subsequent studies also found the same result (119)(120). In typical tumor-induced osteomalacia, symptoms tend to be resolved after removal of the tumor (117).…”
Section: Linear Nevus Sebaceous Syndrome (Lnss)mentioning
confidence: 95%
“…Excision of epidermal lesions with ENS may improve the hypophosphataemic rickets in some patients (47, 56), while it has failed to heal rickets in most patients (115)(116)118). Although it is possible that large amounts of FGF23 are autonomously secreted by LNS lesions, this factor was not found to be directly excreted from the LNS lesions (119). Further study is needed to understand the exact mechanism of how FGF23 is related to hypophosphatemic rickets in LNSS.…”
Section: Linear Nevus Sebaceous Syndrome (Lnss)mentioning
confidence: 99%
“…This neuroectodermal disorder is characterised by involvement of the skeleton and central nervous systems in addition to ophthalmological, cardiovascular, urological and very rarely endocrine abnormalities like precocious puberty and vitamin D-resistant hypophosphataemic rickets. Elevated FGF-23 has consistently been seen in rickets associated with LNSS, but the source of excess FGF-23 still remains debatable 2…”
Section: Descriptionmentioning
confidence: 99%